Produção do espaço residencial em Natal: renda, segregação e gentrificação nos conjuntos habitacionais - Medeiros, Sara Raquel Fernandes Queiroz de (2015)
This thesis analyses the public promotion of residential space in Natal (Brazil), by considering housing policies set up during the BNH (National Housing Bank) and later by both public and private investments. Publicly built housing estates are identified and mapped as well as the collective equipment and infrastructure in place. All that is set against dwellers’s purchasing power to give a measure of segregation and gentrification throuout the years. The discussion considers that the public production of housing estates promoted a striking urban segregation. However, afterwards, those areas benefitted from public and private investments in services and infrastructures. This process added value to them, ultimately causing gentrification. The research considers the year of 1964, when the BNH was set up, as a starting point. The thesis presents a historical view of public policies in Natal. To understand this better, the thesis draws on concepts in so-called political economy of urbanization, in particular that of urban rent. A vast array of documents were analyzed throughout the thesis, including institutional projects, plans, reports, etc. Fieldwork undertaken in 2013-14 considered four major housing estates in Natal: Cidade da Esperança (1967), Soledade (1978), Ponta Negra (1978) e Cidade Satélite (1982). Fieldwork included a sample of 1019 questionnaire interviews with dwellers, land use mapping and photographs. After presenting a brief historical account of their construction and first years of occupation, the researched focused on analysis of data collected. In general, after abandonment during the first years, all housing estates analyzed received considerable investments in public services and infrastructure. According also to what was happening in the city at large, these investments determined that real estate in those estates be valued. This was determining in the social and economic changes which occurred in more recent years – a process of gentrification.